2020
DOI: 10.1111/pan.13905
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of children with urea cycle disorders

Abstract: Background Urea cycle disorders are congenital metabolism errors that affect ammonia elimination. Clinical signs and prognosis are strongly influenced by peak ammonia levels. Numerous triggers associated with metabolic decompensation have been described with many of them, including fasting or stress, being related to the perioperative period. Aims We aimed to assess perioperative complications in pediatric patients with urea cycle disorders requiring general anesthesia in our center. Methods We reviewed the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Any enzymatic defects in the urea cycle inhibit the production of essential amino acids from arginine and cause nitrogen accumulation and hyperammonemia in patients with CPS1D. According to the guidelines for UCD treatment, dextrose and arginine should be administered to suppress protein catabolism and avoid hyperammonemia, in addition to low-protein meals [ 1 , 3 , 4 ]. Although LT is indicated as a final treatment in patients with severe UCD, hyperammonemia is caused by surgical stress [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Any enzymatic defects in the urea cycle inhibit the production of essential amino acids from arginine and cause nitrogen accumulation and hyperammonemia in patients with CPS1D. According to the guidelines for UCD treatment, dextrose and arginine should be administered to suppress protein catabolism and avoid hyperammonemia, in addition to low-protein meals [ 1 , 3 , 4 ]. Although LT is indicated as a final treatment in patients with severe UCD, hyperammonemia is caused by surgical stress [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, serum ammonia was measured every 2 h, and critical hyperammonemia was not observed during surgery. Some reports have suggested that serum ammonia levels should be used as a standard monitor for LT [ 3 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…肝移植手术需要移植科和遗传代谢科等多科室的密切合作,并应在有能力处理高氨血症的医疗机构进行,以应对肝移植术前禁食、全身麻醉、术中出血、术后感染等因素可能诱发的UCD急性发作 [ 2 38 ] 。UCD患儿肝移植围手术期管理旨在防止内源性分解代谢,避免血氨升高 [ 39 - 40 ] 。围手术期患儿应纠正高氨血症,血氨目标浓度为低于80 μmol/L,根据需要维持性给予降氨药物 [ 40 - 41 ] ;尽量安排UCD患儿当日第一台手术,术前需要静脉输注10%葡萄糖,必要时注射脂肪乳以补充能量的需要 [ 9 , 41 ] ;选择合适的麻醉剂有助于手术期间的血氨控制,如OTC缺乏症患儿可使用咪达唑仑、 S -氯胺酮和芬太尼麻醉,保证足够麻醉深度及疼痛控制,血氨水平保持在正常范围内,且神经状态稳定 [ 38 - 39 ] ;术前、术间和术后应密切监测患儿临床症状及血氨水平的变化,术后直至患儿代谢稳定后方可停止静脉葡萄糖输注 [ 9 , 41 ] ;术后还应定期开展多科室随访以全面评估患儿康复情况,并根据相关指标变化调整治疗方案 [ 41 - 42 ] 。…”
Section: 肝移植unclassified